1998
DOI: 10.1002/(sici)1521-4141(199806)28:06<1941::aid-immu1941>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

T cell cross-reactivity to heavy metals: identical cryptic peptides may be presented from protein exposed to different metals

Abstract: The mechanisms by which metals induce activation of T cells and thus produce allergic and/ or autoimmune reactions are still obscure, and the same is true for the mechanisms that underly T cell cross-reactivity to different heavy metal ions. In the present study, we investigated induction by metals of T cell reactions to cryptic peptides of bovine RNase A. Murine CD4+ T cell hybridomas specific for cryptic RNase peptides presented from Au(III)-treated RNase were used as detection probes. We showed that in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 21 publications
0
34
0
1
Order By: Relevance
“…In recent studies Griem and colleagues (17,18) have used bovine RNase A as a model Ag to examine how metals might influence T cell recognition of protein Ags. Immunization of mice with unaltered RNase A or gold-altered RNase A (RNase A/Au(III)) led to a number of T cell hybridomas of varying antigenic specificities (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent studies Griem and colleagues (17,18) have used bovine RNase A as a model Ag to examine how metals might influence T cell recognition of protein Ags. Immunization of mice with unaltered RNase A or gold-altered RNase A (RNase A/Au(III)) led to a number of T cell hybridomas of varying antigenic specificities (17).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of RNase A with a number of other metal ions failed to produce material reactive with the RNase A/Au(III)-specific T cell clones. However a more recent study (18) showed that lead-, platinum-, or nickel-treated bovine RNase A could serve as an Ag for RNase A/Au(III)-specific T cell clones. Although immunization with lead-, platinum-, or nickel-treated bovine RNase A resulted in metal-RNase A specific clones; only one clone, following lead-RNase A immunization, could recognize the cryptic peptide 94 -108.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Case and group studies [4,5] indicate that once locally activated, adaptive immune inflammation to metal contributes to (if not, mediates) the pathogenesis of poor implant performance. Metal DTH reactivity is a lymphocyte mediated response, similar to a Type IV DTH reaction.…”
mentioning
confidence: 99%